Studies of the Metabolism and Distribution of Prothrombin in Healthy Men with Homologous 125I-Prothrombin - Takeda, Y (Thrombosis and Haemostasis, 1972)
A method was described for preparation of purified human prothrombin using repeated barium citrate adsorption and citrate elution, (NH4)2S04 fractionation, Sephadex chromatography and isoelectric precipitation. The produced prothrombins were then physicochemically analyzed. The extinction coefficient was 12.7 ± 0.82 (SD) and the specific activity, 2,563 ± 420 (SD) Iowa units per mg prothrombin. The amino acid composition in g% was as follows: aspartic acid, 8.64; threonine, 5.87; serine, 4.16; glutamic acid, 11.15; proline, 3.91; glycine, 3.96; alanine, 4.65; half cystine, 4.68; valine, 4.46; methionine, 1.14; isoleucine, 2.93; leucine, 6.18; tyrosine, 4.52; phenylalanin, 4.19; lysine, 4.78; histidine, 1.73; ammonia, 1.85; arginine, 6.91. The tryptophan and carbohydrate contents were not determined. The prothrombins were then labeled with 125I in a ratio of about 0.25 atom iodine per molecule of prothrombin and were used for studies of the metabolism and distribution of prothrombin in thirteen healthy men. A model was proposed for the human prothrombin system based on the assumptions that prothrombin is catabolized intravascularly without the formation of thrombin, and was tested against the observed behavior of injected 125I- prothrombin. The model closely predicted the observed behavior of 125I-prothrombin. The analytical results of the tracer data in thirteen healthy men by the methods derived from the model were as follows: The plasma prothrombin, 6.65 ± 1.10 (SD) mg per kg; the interstitial prothrombin, 6.0 ^ 1.9 (SD) mg per kg; the half-life of plasma 125I-prothrombin, 2.29 ± 0.14 (SD) days ; the transcapillary transfer rate of prothrombin, 10.2 ± 3.9 (SD) mg per kg per day; and the catabolic (synthetic) rate of prothrombin, 4.3 J: 1.0 (SD) mg per kg per day. These results support the concept that in healthy men prothrombin is degraded in plasma or spaces in rapid exchange with it generation of appreciable amounts of thrombin.